γH2AX as an Indicator for DNA Double-Strand Breaks in Helicobacter pylori-Associated Chronic Gastritis among Jordanian Patients: A Retrospective Study: γH2AX as an Indicator for DNA damage among Jordanian patients with H. pylori Infection 1 - Ahmad, Mohammad; Al-Zereini, Wael; A. Al-Zeer, Munir (Jordan Medical Journal, 2024)
Background and Aims: Serine 139 phosphorylation of H2AX (γH2AX) is a biomarker for an early response to DNA double-strand breaks (DSB) and to monitor DNA damage and resolution. This study aimed to measure the rate of γH2AX expression associated with H. pylori infection in Jordanian patients with chronic gastritis. Materials and Methods: A retrospective case-control study was designed to evaluate the rate of γH2AX expression in the epithelium of gastric tissue in subjects chronically infected with H. pylori. A total of 75 gastric biopsy samples embedded in paraffin were chosen from the library, including 50 samples with chronic H. pylori infection and 25 negative samples for H. pylori and any other gastric pathologies. PCR and immunohistochemistry were used to confirm the diagnosis of H. pylori-infected and noninfected gastric biopsies, and the rate of γH2AX formation was analyzed in the mucosa using immunohistochemical staining analyses. Results: PCR and immunohistochemistry proved H. pylori infection in the gastric biopsies of diseased patients (n = 50) and the absence of H. pylori infection in negative samples (n = 25). A strong nuclear signal of γH2AX was detected in the positive samples using immunohistochemistry compared to the undetected signal in the noninfected samples of the gastric mucosa. Conclusion: Our findings show that H. pylori infection is accompanied with high levels of DSBs. This may play a role in the increased risk for tumor initiation associated with H. pylori carriage.